PRINSIP HAKIM AKTIF (DOMINI LITIS PRINCIPLE) DALAM PERADILAN TATA USAHA NEGARA - Aju Putrijanti (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Dominis litis principle is one of the important principle in Administrative Court. Judge should be active during the process of the court, gives advise to Plaintiff to complete the claim, also guidance in the evidence process. Due to the development in society, this principle should be understood in a wider sense of substantive and proportional justice. To gives substantive and proportional justice, judge should consider ethic,moral, customs, and others outside law itself, and have to think progressive , in order to give a substantial justice. Refer to this principle, it is shown that there is an important relation between the domini litis principle, and a substantive proportional justice, as should be understood in a progressive way. Keywords :domini litis principle, administrative court. Abstrak Prinsip hakim aktif adalah salah satu prinsip penting dalam pemeriksaan di Peradilan Tata Usaha Negara. Hakim secara aktif, menasehati Penggugat untuk melengkapi surat gugatan, serta dalam proses pembuktian. Dalam perkembangan di masyarakat, prinsip hakim aktif perlu untuk dipahami secara luas, untuk dapat memberi keadilan substansial proporsional. Hakim harus mempertimbangkan faktor moral, etika, kebiasaan dan faktor-faktor non hukum lainnya untuk mewujudkannya.Antara prinsip hakim aktif dan keadilan substansial proporsional ada keterkaitan yang penting, serta harus dipahami sebagai cara berpikir yang bersifat progresif. Kata kunci: prinsip hakim aktif, peradilan tata usaha negara.